An in silico molecular strategy to uncover medication against SARS CoV-2 from coastal grass Spinifex littoreus (Burm f.) Merr. - Vedhamani, J; Ajithkumar, I P (Plant Science Today, 2025)
The coronavirus (COVID-19) caused a global public health disaster and every outbreak is believed to have a natural cure. Hence, this investigation aims to identify a suitable target to inhibit viral multiplication using Spinifex littoreus and to control the binding of human ACE2 receptors with the viral protein through molecular docking. This investigation aids in finding a SARS-CoV-2 antagonist in the coastal grass S. littoreus. Through GC-MS analysis, 22 different phytochemical compounds were screened from the methanolic and chloroform extracts of S. littoreus. Using Swiss ADME software, the drug-likeness properties of the screened compounds were examined. Of the 22 screened compounds, only seven adhere to Lipinski's rule of five. The compound 1-methylene-2b-hydroxymethyl-3,3-dimethyl-4b -(3-methylbut-2-enyl)-cyclohexane was docked against 3CLPRO and the spike (S) glycoprotein of SARS-CoV-2. The free binding energies of the target proteins are -6.12 kcal/mol and -6.0 kcal/mol, respectively. A stronger ligand -protein interaction results in lower binding energy. These findings could contribute to the development of a new medication for the treatment of SARS-CoV-2.